Impact of mandibular implant prostheses on the oral health-related quality of life in partially and completely edentulous patients - Yunus, N.; Masood, M.; Saub, R.; Al-Hashedi, A.A.; Taiyeb-Ali, T.B.; Thomason, J.M. (Blackwell Publishing, 2015)
Objective: To assess the oral health-related quality of life (OHRQoL) of patients provided with mandibular implant fixed partial prostheses (IFPP) for rehabilitation of two adjacent missing posterior teeth and complete denture patients provided with mandibular implant-supported overdenture (ISOD). The response to change in OHRQoL with implant prostheses was additionally compared. Material and methods: In this prospective study, 20 IFPP (mean age 47.0; SD 12.9 years) and 28 ISOD (mean age 61.5; SD 9.1 years) patients received 2 mandibular implants. Metal ceramic nonsplinted fixed prostheses were provided in IFPP group, while in ISOD group, the mandibular overdentures were retained by nonsplinted attachments. Patients rated their oral health-related quality of life using OHIP-14 Malaysian version at baseline (T0), 2–3 months (T1) and 1 year (T2) postimplant treatment. Mean OHIP-14 for total and domain scores between groups and intervals was analysed using repeated-measures ANOVA and t-test. Mann–Whitney and Wilcoxon signed–rank tests were used for the comparison of mean score change and effect size, while the association between pre- and post-treatment scores was determined using multivariate linear regression modelling. Results: The total OHIP and domain scores before implant treatment were significantly higher (lower OHRQoL) in IFPP than in ISOD groups, except for physical pain where this domain showed similar impact in both groups. Postimplant scores between groups at T1 and T2 showed no significant difference. The mean score changes at T0–T1 and T0–T2 for total OHIP-14 and domains were significantly greater in IFPP except in the domains of physical pain and disability which showed no difference. Large effect size (ES) was observed for total OHIP-14 in IFPP while moderate in ISOD. Improved OHRQoL was dependent on the treatment group and pretreatment score. Conclusion: Improvement in OHRQoL occurred following both mandibular implant-supported overdentures and implant fixed partial prostheses.